Geminivirus infecting pepper: symptom variation and transmission study Infection of geminiviruses has been reported to cause signz3cantyield loss on various crops. Polymerase chain reaction was able to detect geminivirus infection on pepper samples around Bogor and Cipanas, West Java. Symptom variation and transmission of the geminivirus infectingpepper was studied using five solanaceae plants with three dzgerent transmission mannec i.e. mechanical inoculation, side grafirng, and insect vector. - Eliza S. Rusli; Sri H. Hidayat; Rusmilah Suseno; Budi Tjahjono (Buletin Hama dan Penyakit Tumbuhan, 1999)
Geminivirus infecting pepper: symptom variation and transmission study Infection of geminiviruses has been reported to cause signz3cantyield loss on various crops. Polymerase chain reaction was able to detect geminivirus infection on pepper samples around Bogor and Cipanas, West Java. Symptom variation and transmission of the geminivirus infectingpepper was studied using five solanaceae plants with three dzgerent transmission mannec i.e. mechanical inoculation, side grafirng, and insect vector. The transmission study showed that mechanical inoculation was not able to transmit the eminivirus, while side grafting and insect vector, Bemisia tabaci, caused infection with symptoms varies from yellow mosaic, leaf curl leaf distortion, to stunting of the plant. Higher infection was observed on pepper var. Hot Chilli through B. tabaci (8009) and side grafting (71.4%) than those on chilli pepper and tomato. DNA fiagment of - 1.7 kb was amplified wing PCRfim those plants showing symptoms, but no DNA fiagment was observedfrom symptomless eggplant and tobacco var. White Burley. Thus it can be concluded that the last two kina3 ofplants were resistant to the geminivirus infectingpepper.